2021
DOI: 10.3390/ijerph182312418
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion from Social Relations in Later Life: Micro- and Macro-Level Patterns and Correlations in a European Perspective

Abstract: Older adults face particular risks of exclusion from social relationships (ESR) and are especially vulnerable to its consequences. However, research so far has been limited to specific dimensions, countries, and time points. In this paper, we examine the prevalence and micro- and macro-level predictors of ESR among older adults (60+) using two waves of data obtained four years apart across 14 European countries in the Survey of Health, Ageing and Retirement in Europe (SHARE). We consider four ESR indicators (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The overall patterns in the prevalence of loneliness appeared entrenched already before the emergence of the pandemic, and increased slightly but ubiquitously during its early phase, and specifically by residential setting. This differential impact, rooted in underlying social inequalities, expands previous findings of increased inequalities in loneliness by gender ( Hansen et al, 2021 ) and in social contacts by residential setting ( Freedman et al, 2021 ) during the pandemic. Taken together, it provides a complex picture of social vulnerability and resiliency among older adults, which stands in stark contrast to common depictions and empirical approaches treating older adults as one homogenous vulnerable group.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The overall patterns in the prevalence of loneliness appeared entrenched already before the emergence of the pandemic, and increased slightly but ubiquitously during its early phase, and specifically by residential setting. This differential impact, rooted in underlying social inequalities, expands previous findings of increased inequalities in loneliness by gender ( Hansen et al, 2021 ) and in social contacts by residential setting ( Freedman et al, 2021 ) during the pandemic. Taken together, it provides a complex picture of social vulnerability and resiliency among older adults, which stands in stark contrast to common depictions and empirical approaches treating older adults as one homogenous vulnerable group.…”
Section: Discussionsupporting
confidence: 79%
“…While higher loneliness with increasing age has indeed been reported among the oldest old ( Niedzwiedz et al, 2016 ), a recent meta-analysis showed similar levels of loneliness among older and younger older adults ( Chawla et al, 2021 ). Gender inequalities in loneliness among older adults display a complex and context-dependent pattern, with similar or higher levels of loneliness, as well as greater impact of the COVID-19 pandemic ( Hansen et al, 2021 ), among older women compared to older men ( Cohen-Mansfield et al, 2016 ; Pinquart and Sorensen, 2001 ). Economic inequalities in loneliness, with greater loneliness among older adults with lower income or wealth ( Bosma et al, 2015 ; Niedzwiedz et al, 2016 ), have been hypothesized to reflect poorer opportunities to develop relationships during working age, the direct financial barrier to social activities, and indirect barriers due to income-related inequalities in health and functional limitations ( Niedzwiedz et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these individual characteristics, country-specific characteristics also explain higher risks of loneliness. Macro-level demographic and economic factors, inequalities, cultural norms and values, levels of safety, and the existence and extent of public and social policies are among the country-specific characteristics that were found to be associated with social isolation and loneliness [ 32 , 33 , 83 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, loneliness ("feeling alone") is a subjective experience and refers to the negative feeling caused by a discrepancy between actual and desired social connection and social contact [5,11,12]. The prevalence of social isolation varies across its speci c indicators, but generally increases in later life [13]. For instance, over one-third of adults aged 65 and above, and more than half of those aged over 80, live alone in Norway and several other Western countries [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of social isolation varies across its speci c indicators, but generally increases in later life [13]. For instance, over one-third of adults aged 65 and above, and more than half of those aged over 80, live alone in Norway and several other Western countries [13,14]. Loneliness is also a widespread issue in Western countries, with approximately one-quarter of the adult population reporting that they "sometimes" or "often" feel lonely [15,16].…”
Section: Introductionmentioning
confidence: 99%